A fluorinated aza-BODIPY derivative for NIR fluorescence/PA/19F MR tri-modality in vivo imaging. Issue 42 (30th April 2019) - Liu, Lianhua; Yuan, Yaping; Yang, Yuqi; McMahon, Michael T.; Chen, Shizhen; Zhou, Xin
Abstract : A fluorinated aza-BODIPY derivative BDPF was developed as a small molecule contrast agent, which displayed highly efficient near infrared fluorescence/photoacoustic/ 19 F MR tri-modality tumor imaging. Abstract : A fluorinated aza-BODIPY derivative BDPF was developed as a small molecule contrast agent, which displayed highly efficient near infrared fluorescence/photoacoustic/ 19 F MR tri-modality tumor imaging.